Endurance capacity and selected technical-tactical skills of soccer players participating in the group stage of the 2014 FIFA World Cup - Chmura, Paweł; Goliński, Dawid; Andrzejewski, Marcin; Mroczek, Dariusz; Kawczyński, Adam; Rokita, Andrzej; Chmura, Jan (Akademia Wychowania Fizycznego w Poznaniu)
The study examines the endurance capacity and selected technical-tactical skills of soccer players participating in the2014 World Cup in Brazil. The results indicate the significant impact of players’ motor preparation level on the execution of technical-tactical actions in top-class soccer tournaments. The covered distance by players during a match is one of the most important indices used for assessment of players’ endurance capacity. The analysis revealed that the Spain and Italy national teams which attained very high passing efficiency and total number of passes failed to advance to the knockout stage of the tournament. The analysis of the structure of match performance, especially by elite teams, is necessary for rational programming of endurance training in professional soccer. The knowledge of endurance loads at top-level soccer tournament permits the optimalization of modern soccer training
Keywords: soccer; endurance; covered distance; ball possession; completed passes; World Cup 2014